Alterations in the gut microbiota of patients with acquired immune deficiency syndrome. Issue 4 (7th February 2018) - Zhou, Youlian; Ou, Zhitao; Tang, Xiaoping; Zhou, Yongjian; Xu, Haoming; Wang, Xianfei; Li, Kang; He, Jie; Du, Yanlei; Wang, Hong; Chen, Ye; Nie, Yuqiang
Abstract: Acquired immune deficiency syndrome (AIDS), caused by infection with human immunodeficiency virus (HIV), is associated with gastrointestinal disease, systemic immune activation and changes in the gut microbiota. Here, we aim to investigate the gut microbiota patterns of HIV‐infected individuals and HIV‐uninfected individuals in populations from South China. We enrolled 33 patients with HIV (14 participants treated with highly active antiretroviral therapy [HAART] for more than 3 months; the remaining 19 individuals had not received treatment) and 35 healthy controls (HC) for a cross‐sectional comparison of gut microbiota using stool samples. Gut microbial communities were profiled by sequencing the bacterial 16S rRNA genes. Dysbiosis was more common among patients with AIDS compared with healthy individuals. Dysbiosis was characterized by decreased α‐diversity, low mean counts of Bacteroidetes, Faecalibacterium, Prevotella, Bacteroides vulgatus, Dialister and Roseburia inulnivorans, and high mean counts of Proteobacteria, Enterococcus, Streptococcus, Lactobacillus, Lachnociostridium, Ruminococcus gnavus and Streptococcus vestibularis . Increased abundance of Bacilli was observed in homosexual patients. Proteobacteria were higher among heterosexual patients with HIV infections. Tenericutes were higher among patients with history of intravenous drug abuse. Restoration of gut microbiota diversity and a significant increase in abundance of Faecalibacterium, Blautia and Bacteroides were found in patients receiving HAART compared to those who did not receive. HIV infection‐associated dysbiosis is characterized by decreased levels of α‐diversity and Bacteroidetes, increased levels of Proteobacteria and the alterations of gut microbiota correlate with the route of HIV transmission. The imbalanced faecal microbiota of HIV infection is partially restored after therapy.